Sociabilidad y Francmasonería. Propuestas para una historia de las prácticas sociales y culturales en el Siglo de la Luces - Beaurepaire, Pierre-Yves (2013)
A laboratory of observation and renovation of sociability, mirroring elites, their strategies and individual journeys, Masonic Lodges flourish during the Enlightenment. Significantly, in the 18th century, the lodge of Perpignan brought together the city’s elite under the chosen name of : La Sociabilité. A place of initiation, the Masonic fraternity creates rich social bonds with their teachings. Georg Simmel, Maurice Agulhon and Daniel Roche have enabled remarkable progress in the research of sociability. The former has studied the relation of this lodge with the secret; the following scholar has analysed the transition between brotherhoods of penitents and Masonic lodges; and the latter has delivered a very accurate picture of Enlightenment’s sociability. This article makes both a balance of previous research and proposes the exploration of further depths and new perspectives.